THE EFFECT OF MINDFULNESS THERAPY ON ENVIRONMENTAL ADAPTATION ANXIETY IN NEW FEMALE STUDENTS AT THE DARUL HIKMAH BALEN ISLAMIC BOARDING SCHOOL, BOJONEGORO BASED ON ROY'S ADAPTATION THEORY - Syani Laily Anggrina; Evita Muslima Isnanda Putri; Agus Ari Afandi; Sri Mulyani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
New female students at Islamic boarding schools often experience environmental adaptation anxiety due to significant changes in their social environment and lifestyle. This condition can affect their emotional balance, learning process, and adjustment abilities. Mindfulness therapy is known as a non-pharmacological intervention that can improve emotional regulation and reduce anxiety. This study aims to analyze the effect of mindfulness therapy on environmental adaptation anxiety in new female students at Darul Hikmah Balen Islamic Boarding School in Bojonegoro based on Roy's Adaptation Theory. The study used a quantitative pre-experimental design with a one-group pretest-posttest approach. The study population consisted of 23 new female students, with a sample of 20 respondents selected using purposive sampling. Data collection used a mindfulness therapy module and the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was performed univariately and bivariately using the Friedman test in SPSS 20.0. The results showed that before the intervention, 85% of respondents experienced severe anxiety. After four sessions of mindfulness therapy for two weeks, all respondents (100%) experienced mild anxiety. The statistical test results showed a p-value of 0.000 (<0.05), indicating a significant effect of mindfulness therapy on environmental adaptation anxiety. The conclusion of this study is that mindfulness therapy is effective in reducing environmental adaptation anxiety in new female students at Islamic boarding schools.